Book review: Bordyuzha, N. N., et al. (Eds.). (2022). Sustainability and Security Analytics of Greater Eurasia. The Image of the Future: Threats, Challenges and Risks: II Eurasian Analytical Forum: Collection of reports of the plenary session and analytical session “Information and analytical support for socio-economic development of the Eurasian Economic Union at the present stage”, Minsk, November 11, 2021. International University “MITSO”. Minsk: MITSO publ., 388 p. (In Russian) - Komron Kh. Rakhimov (Vestnik RUDN. International Relations, 2023)
-